PERSON DEIXIS USED IN THE PURSUIT OF HAPPYNESS MOVIE - Barus, Jumat (Universitas Islam Sumatera Utara (UISU), 2023)
Deixis plays a crucial role in language by pointing or referring to specific people, places, or times. The study specifically focuses on personal deixis, which is essential for effective communication in daily conversations, as it helps avoiding misunderstandings regarding references made by the speaker. The objective of this study is to analyze the types of deixis present in the movie The Pursuit of Happyness. This research uses a descriptive qualitative analysis method. The data collected for analysis follow thematic analysis which is a qualitative data analysis that focuses on identifying, analyzing, and interpreting data. The findings of this research reveal numerous instances of deixis in the movie. Among the 898 instances of personal deixis identified, singular first-person deixis accounts for 180 occurrences, plural first-person deixis 107 instances, singular second-person deixis 375, singular third-person deixis 195, and plural third-person deixis 33. This study contributes to the understanding of deixis in movie discourse and provides insights into the pragmatic use of language in the movie. It enhances our knowledge of how deixis functions within a specific cinematic context and highlights the significance of personal deixis in shaping effective communication. The findings can be valuable for linguistic analysis, film studies, and contribute to the broader understanding of deixis in various forms of media.